"It's not the same without you:" Exploring the experience and perception of transition for people with intellectual disabilities and dementia. - Sheth, Alisa Jordan; Kramer, Jessica M.; Magasi, Susan; Heller, Tamar; Nishida, Akemi; Hammel, Joy (British Journal of Learning Disabilities, 2021)
Accessible Summary: This project focuses on people with intellectual disabilities and dementia that live in group homes or care facilities in the United States.People in this project shared how their life changed as they got older. They talked about where they live, what they do for work and how they get to spend their day.All the people in this project talked about how it was important for them to see their friends, even if where they lived or worked changed.People in this project worried that they would have to move or stop doing activities that were important to them if they started to need more help.People with intellectual disabilities and dementia should receive support to continue to see friends and do their favourite activities as they get older. Background: For people with intellectual disabilities and dementia, transitions are likely to become increasingly common as they age. While transitions experienced by people with intellectual disabilities in young adulthood are frequently studied, less is known about transitions in older adults, including residential, vocational and leisure changes. This article aims to explore the experiences of transition from the perspectives of people with intellectual disabilities and dementia, including the impact on their daily lives. Methodology: Three women with intellectual disabilities and dementia living in residential settings participated in participant observations and informal interviews across a variety of environments and activities. Field notes and interview transcripts underwent a thematic analysis focusing on transitions. Findings: Participants experienced the impact of transitions in their residential placements, day programming, leisure activities and relationships. Themes related to their experiences of transitions included making sense of transitions, utilising peer care networks for support and tackling the looming threat of loss and transition. Conclusions: Peer care networks and friendships are crucial in supporting people during and after transitions. Receiving effective supports to maintain relationships, roles and activities, even in seemingly minor ways, is an important right for people with intellectual disabilities and dementia, particularly as care needs increase.